PENGARUH SUBSTITUSI LIMBAH KACA TERHADAP TENSILE STRENGTH RATIO CAMPURAN BERASPAL ASPHALT CONCRETE-BINDER COURSE - Syaripin; Suparma, Latif Budi; Mulyono, Agus Taufik; Alawy, Gholiqul Amrodh; Ardiansyah, Ahmad Farid; Septiandri, Rohmahillah Aviskanasya (Jurnal HPJI (Himpunan Pengembangan Jalan Indonesia), 2025)
Abstract Hot asphalt mixtures require aggregate as the constituent material. In this study, the potential for glass waste to be used as an aggregate substitute is examined. For this reason, a mixture design was determined to obtain the Optimum Asphalt Content of the Asphalt Concrete-Binder Course mixtures using glass waste as a substitute for fine aggregate. The glass waste used is glass waste that passes through sieve No. 50 and retained on sieve No.100. The proportion of glass waste substitution is 0%, 25%, 50%, 75%, and 100% to the amount of fine aggregate in the mixture. The asphalt mixture in this study was made using the Marshall mixture design method. From this design, the Optimum Asphalt Content is obtained at 5.9% (0% glass waste), 5.4% (25% glass waste), 5.2% (50% glass waste), 5.1% (75% glass waste), and 4.9% (100% glass waste). Next, test spe-cimens were made for Indirect Tensile Strength testing, and carried out for testing in dry and wet conditions, and the Tensile Strength Ratio of the test specimens was determined. The Tensile Strength Ratio of the asphalt mixture decreases with increasing proportion of glass waste and decreasing asphalt content. Overall, this research shows that glass waste can be used as a substitute for fine aggregate. Keywords: hot mix asphalt; aggregate; glass waste; Marshall Method; Tensile Strength Ratio Abstrak Campuran beraspal panas memerlukan agregat sebagai material penyusunnya. Pada studi ini dikaji potensi limbah kaca untuk dimanfaatkan sebagai substitusi agregat. Untuk itu ditentukan rancangan campuran dengan untuk mendapatkan Kadar Aspal Optimum pada campuran beraspal jenis Asphalt Concrete-Binder Course dengan menggunakan limbah kaca sebagai substitusi agregat halus. Limbah kaca yang digunakan adalah limbah kaca yang lolos ayakan No. 50 dan tertahan ayakan No.100. Proporsi substitusi limbah kaca adalah 0%, 25%, 50%, 75%, dan 100% terhadap jumlah agregat halus dalam campuran. Campuran beraspal pada studi ini dibuat dengan menggunakan metode perancangan campuran Marshall. Dari perancangan tersebut diperoleh Kadar Aspal Optimum sebesar 5,9% (limbah kaca 0%), 5,4% (limbah kaca 25%), 5,2% (limbah kaca 50%), 5,1% (limbah kaca 75%), dan 4,9% (limbah kaca 100%). Selanjutnya dibuat benda-benda uji untuk pengujian Indirect Tensile Strength, dan dilakukan untuk pengujian dengan kondisi telah dilakukan pengkondisian kering dan kondisi basah, serta ditentukan Tensile Strength Ratio benda-benda uji. Tensile Strength Ratio campuran beraspal mengecil dengan bertambahnya proporsi limbah kaca dan berkurangnya kadar aspal. Secara keseluruhan, penelitian ini menunjukkan bahwa limbah kaca dapat dimanfaatkan sebagai substitusi agregat halus. Kata-kata kunci: campuran beraspal panas; agregat; limbah kaca; Metode Marshall; Tensile Strength Ratio